P3.173 STI Screening and Diagnosis History Among Women Who Have Sex with Women and Men. (13th July 2013) - Schick, V R; Bell, A; Neal, C; Pol, B Van Der; Dodge, B; Fortenberry, J D
Abstract : Background: Research suggests that bisexually-identified women may be more likely to report an STI diagnosis within their lifetime than women who identify as heterosexual or homosexual. In the present study, the role of behaviour and identity were explored in relation to self-reported STI screening and diagnosis history. Methods: Behaviorally bisexual women (defined as genital contact with a male and female partner within the past 12 months) were recruited through websites, flyers, community events and participant referrals. Participants were asked to complete an on-line survey and an in-person interview. Participants self-reported details of sexual behaviours, sexual orientation/identity, STI screening and STI diagnosis history. They were also given the option to provide self-collected vaginal, oral, and anal samples for STI screening. Results: Participants (N = 80) ranged in age from 18 to 51 (M = 26.74, SD = 7.97). Over three-quarters of the participants reported a history of STI screening. Over a quarter of the participants who reported screening reported a diagnosis of Chlamydia, HPV and/or bacterial vaginosis. Participants who identified as bisexual were more likely to report STI screening than their counterparts. The majority of participants provided a vaginal, oral, and/or anal sample for STI screening. None of the participants tested positive for Trichomoniasis or Gonorrhea with approximately 7% of participants testing positive for Chlamydia. Conclusion: The majority of participants reported STI screening with a sizable minority of participants reporting a positive STI diagnosis. The high proportion of participants who provided a vaginal, oral and/or anal sample indicates a high acceptability rate. The relationship of identity to STI screening in a sample of WSWM highlights the complexity of interventions targeted towards populations defined solely by identity or behaviour.